Changing World Order, Student Movement and Radicalism - Azis Andriansyah; Retno Saraswati; Irma Cahyaningtyas; Sukirno Sukirno (Budapest International Research and Critics University, 2022)
The development of ideology influenced the Indonesian student movement from period to period. By looking at the history of the movement in Indonesia, we can see that students are the motor of the movement. Students become agents of change who can change the direction of a change, bring down the ruling regime and create regime change. This paper tries to see the influence of the world order on the student movement. How does a foreign policy or an ideology spread and enter Indonesia? This paper looks at the student movement since the ethical politics that developed in the Netherlands led the Dutch to establish high schools and thus start the Indonesian student movement. Then how do these student movements continue to develop so that, in the end, youth have an essential role in realizing Indonesian independence? Do not stop until the achievement of independence. The student movement tried to realize the ideals of Indonesia through various criticisms of various regimes. In the end, this paper looks at how the existence of the internet and globalization affect the student movement. This research shows that changing times can spread ideas. The spread of this idea is getting faster and unstoppable in the age of information technology. Therefore at this time, good ideologies and destructive ideologies such as radicalism can spread without being seen by the eye. Currently, various stakeholders need various efforts to direct students so that they do not fall into radicalism.